Earthquakes. - World Book, Inc. (Chicago : World Book, 2009)
"A discussion of a major type of natural disaster, including descriptions of some of the most destructive; explanations of these phenomena, what causes them, and where they occur; and information about how to prepare for and survive these forces of nature. Features include an activity, glossary, list of resources, and index"--Provided by publisher.
What is an earthquake? -- Drifting plates -- The San Francisco earthquake -- Seismic waves -- Earthquake scales -- What happens during an earthquake? -- The Armenian earthquake of 1988 -- Earthquake and fire in Tokyo -- The Kobe earthquake -- Sinking into the earth -- The Mexico City earthquake -- Tsunamis -- The Lisbon earthquake of 1755 -- Landslides and floods -- Avalanche in the Andes -- The Tangshan earthquake -- An earthquake in the Himalayas -- The Chilean earthquake -- Monitoring and predicting earthquakes -- Preparing for earthquakes.
Includes bibliographical references (p. 47) and index.
Keywords: Earthquakes -- Juvenile literature